Cholesterol Serum Levels and Use of Statins in Graves' Orbitopathy: A New Starting Point for the Therapy - Lanzolla, Giulia; Vannucchi, Guia; Ionni, Ilaria; Campi, Irene; Sileo, Federica; Lazzaroni, Elisa; Marinò, Michele (Frontiers in Endocrinology, 2020)
Graves’ Orbitopathy (GO) is the most frequent extrathyroidal manifestation of Graves’ disease (GD). Its ultimate cause remains unclear, but it is commonly considered an autoimmune disorder due to self recognition of autoantigens constitutively expressed by orbital fibroblasts (OFs) and thyroid epithelial cells. High dose intravenous glucocorticoids (ivGC) are the most commonly used treatment for moderately severe and active GO. However, based on the complex pathogenesis of GO, a number of factors may have a protective and maybe a therapeutic role. The use of other medications improving the effect of GC may increase the overall effectiveness of the therapy and reduce GC doses, thereby limiting side effects. Recently, a possible protective role of 3-hydroxy-3-methylglutaryl-coenzyme reductase inhibitors, the so-called statins, and perhaps of lowering cholesterol levels, has been proposed. Thus, statins have been reported to be associated with a reduced frequency of GO in GD patients and in recent cross-sectional and retrospective studies a significant correlation was found between the occurrence of GO and both total and LDL-cholesterol in patients with a GD of relatively recent onset, suggesting a role of cholesterol in the development of GO. Moreover, a correlation was found between the GO clinical activity score and total as well as LDL-cholesterol in untreated GO patients, depending on GO duration, indicating a role of cholesterol on GO activity. Therefore, statin treatment may be beneficial for GO. Here we review this subject, which offers new therapeutic perspectives for patients with GO.